19. Identification of Ectoparasites in the Mud Crab (Scylla serrata) from Alue Naga Coastal Waters Banda Aceh - Audi Maldini; Winaruddin Winaruddin; Muttaqien Bakri; Muhammad Hambal; Farida Farida; Razali Daud (Jurnal Medika Veterinaria, 2017)
This study aimsed  to determine the type of ectoparasites on crab (Scylla serrata) in the water of Alue Naga Banda Aceh.  The samples of this study were 10 heads of mud crabs were taken from the Alue Naga waters Banda Aceh and taken to the Laboratory of Parasitology. Veterinary Medicine Faculty of Syiah Kuala University Banda Aceh to identify the take ectoparasites on mud crab (Scylla serrata) by observing the outer body of the organism, then noted bleeding, wounds or swelling and pay attention to the type of organism that is attached to the body of mud crab, then dredge the outer parts of the body like the carapace, foot path, foot pool and gills were take it and then tweezers and then putting the object glass that has been provided and observed with a microscope with 100 times magnification and see what kind of ectoparasites that have been found and then compare with the identification key. From the results of this study concluded that ectoparasites which infects mud crab (Scylla serrata) in the waters of Alue Naga Banda Aceh come  from genus Chilodonella sp. Whichare predilections in the gills with a prevalence rate of 10%.